Detrimental predictive effect of metabolic syndrome on postoperative complications in patients who undergoing coronary artery bypass grafting - Gharipour, Mojgan; Sadeghi, Mohsen Mirmohammad; Sadeghi, Masoumeh; Farhmand, Niloufar; Sadeghi, Pouya Mirmohammad (Acta Biomedica Atenei Parmensis, 2015)
Background: The present study came to address the value of metabolic syndrome (MetS) in predicting postoperative outcome following coronary artery bypass grafting (CABG). Methods: In a retrospective study, a consecutive series of patients including 2010 subjects who underwent isolated CABG were reviewed. Baseline information and intraoperative details were collected by reviewing hospital-recorded files. The composite outcome of major adverse cardiac and cerebrovascular events (postoperative morbidity) was generated from the occurrence of myocardial infarction, cardiac arrhythmias, stroke, renal failure, and other cardiac-related problems. Results: Overall, 2010 patients who underwent isolated CABG were studied that among them 24.7% suffered from MetS. No difference was found in the prevalence of postoperative arrhythmias, brain stroke, multi-organ failure, and dialysis between the two groups with and without MetS. Early morbidity rate was 27.4% in MetS group and 27.8% in non-MetS group with no significant discrepancy. Using multivariable logistic regression modeling, we showed that MetS status could not predict postoperative morbidity; however, advanced age, history of congestive heart failure, higher Canadian Cardiovascular Society (CCS) scale, and longer cross-clamp time were main indicators of postoperative morbidity. Conclusion: MetS has no detrimental predictive effect on early postoperative morbidity in CABG patients. (www.actabiomedica.it)